The problem of novel FVIII missense mutations for haemophilia A genetic counseling - Schneppenheim, R.; Schröder, J.; Obser, T.; Oyen, F.; Schneppenheim, S.; Oldenburg, J. (Hämostaseologie, 2009)
Molecular genetic testing for factor VIII (FVIII) mutations is indicated in haemophilia A since determination of FVIII activity cannot reliably identify female carriers. Given the large number of FVIII mutations the identification of novel mutations is not uncommon. Since amino acid polymorphisms of FVIII are rare, missense mutations in patients with haemophilia A which are not found in the normal population are considered as causative in general practice when no other mutation can be detected by complete FVIII gene sequencing.We report a novel rare missense variant (P2311S) in a haemophilia A family that was mistakenly considered as pathogenic leading to amniocentesis, prenatal diagnosis and influenced the peripartal management of the putatively affected child. Subsequently, we identified the novel causative mutation V197G in the family‘s index case which could be detected neither in the neonate nor in his mother. Conclusion: This case emphasizes the necessity to establish the molecular diagnosis in the family‘s index case and to perform expression studies of novel mutations to prove their causative nature.
Keywords: Factor VIII; haemophilia A; molecular genetics; recombinant FVIII